Reproduction of society through education - Štrajn, Darko (Šolsko polje, 2012)
Whenever we mention the very term "reproduction" in the context of education, we cannot avoid the seminal work of Pierre Bourdieu and Jean- Claude Passeron,simply entitled Reproduction. As implied in their book, it is necessary to construct a system of relations between the educational system and the other sub-systems. A relative autonomy of the educational system is always "the counterpart of a dependence hidden to a greater or lesser extent by the practices and ideology authorized by that autonomy". The problem of the functioning of an educational system in this regard is a matter of much dispute. It is far more important how a school system functions than how its role in a society is declared. Most of the national education systems are declared as being open to everyone, but they eff ectively result in segregation, usually on the basis of a pupil's social class. Policy-makers and researchers of education are caught in the crossfire of controversies that cannot be easily solved. Bourdieu's and Passeron's work should still be remembered due to its paradigmatic and theoretical importance, transcending the limits of the time when it was published. The discursive fi eld, formed by educational system interacting with other systems within a society, is structured by reproductive projections and schemes, which contain incorporating agencies. Social expectations from education in the lower social strata are hindered by many dominant views concerning pupil's social origin. In the era of late neo-liberal domination, there are symptoms, which expose counter tendencies against a definition of education as a "big social equaliser" and as an instrument of social upward mobility. A recent film, Anonymous (2011) by Ronald Emerich, which is built on the myth of Shakespeare's non-authorship, is a case in point.
Keywords: education; vzgoja in izobraževanje; družba; society; šole; school; ideologija; ideology; moč; power; raziskave; research; Shakespeare